2011
DOI: 10.1029/2011jb008649
|View full text |Cite
|
Sign up to set email alerts
|

Porosity evolution and crystallization-driven fragmentation during weathering of andesite

Abstract: [1] A 10 m thick andesitic sill intrusion from the Neuquén Basin, Argentina, shows spectacular examples of spheroidal weathering and Liesegang banding. The Liesegang patterns demonstrate how andesite blocks, initially cut out by a preweathering joint set, are subdivided by fractures formed during the spheroidal weathering process. The stresses that cause fracturing originate from the growth of ferrihydrite and calcite in the pore space of the andesite, partly at the expense of original ilmenite, amphibole, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 30 publications
1
49
0
Order By: Relevance
“…Oxidative weathering produces a specific volume increase of the solid material and thus builds up strain that fractures the rock. Similarly, precipitation of secondary clay minerals following dissolution of primary minerals was also proposed to result in strain build-up and rock fracturing (Jamtveit et al, 2011;Jamtveit et al, 2008;Røyne et al, 2008;Rudge et al, 2010). In contrast to pathways that require the generation of strain, the access of reactive phases from the surface to the weathering front might also be promoted by the formation of secondary porosity by primary mineral dissolution and precipitation of secondary minerals with a lower molar volume (Lebedeva et al, 2007;Navarre-Sitchler et al, 2011;Sak et al, 2010;Velbel, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative weathering produces a specific volume increase of the solid material and thus builds up strain that fractures the rock. Similarly, precipitation of secondary clay minerals following dissolution of primary minerals was also proposed to result in strain build-up and rock fracturing (Jamtveit et al, 2011;Jamtveit et al, 2008;Røyne et al, 2008;Rudge et al, 2010). In contrast to pathways that require the generation of strain, the access of reactive phases from the surface to the weathering front might also be promoted by the formation of secondary porosity by primary mineral dissolution and precipitation of secondary minerals with a lower molar volume (Lebedeva et al, 2007;Navarre-Sitchler et al, 2011;Sak et al, 2010;Velbel, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Spheroidal weathering, the process that produces concentric, onion-skin type weathering rinds around bedrock corestones (Chapman and Greenfield, 1949), is an extensively explored process converting bedrock into weathered material, and thereby may set the advance rate of the weathering front in a wide range of settings (Sak et al, 2004(Sak et al, , 2010Fletcher et al, 2006;Royne et al, 2008;Buss et al, 2008). Several mechanisms have been suggested for spheroidal weathering, and most of these involve fracturing induced by local strain that is caused by several processes: 1) mineralogical transformations involving volume change such as the oxidation of ferrous minerals, mostly biotite (Fletcher et al, 2006;Lebedeva et al, 2007; 2) the precipitation of secondary minerals therein, thereby generating stress and fracturing (Røyne et al, 2008;Jamtveit et al, 2009Jamtveit et al, , 2011; 3) or the utilization of mesofractures by fungal hyphae that supply water and mineral-dissolving reagents (Graham et al, 2010). The spacing of initial fractures bounding corestones (Fletcher and Brantley, 2010), and of those formed by positive strain during spheroidal weathering (Fletcher et al, 2006) have been identified as a key control over the rate of weathering front advance.…”
Section: Introductionmentioning
confidence: 99%
“…Domain III is further subdivided into IIIA and IIIB, before IIIA split into twins IIIAa and IIIAb. The brown coloured striation is a combination of Liesegang bands and onion skin fractures (slightly modified from Jamtveit et al, 2011). Figure 8.2 shows a block of andesite, originally cut out by perpendicular joints probably formed during thermal contraction of the andesitic sill intrusion of which the block is a part.…”
Section: Figure 82mentioning
confidence: 99%
“…The porosity is characterised by a high frequency of narrow pore throats, with a maximum frequency ~20 nm and a maximum value ~200 nm ( Fig. 8.3; more details presented in Jamtveit et al, 2011).…”
Section: Figure 82mentioning
confidence: 99%
See 1 more Smart Citation